2012
DOI: 10.1186/2192-0567-2-21
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emission reductions as a motivator of e85 purchases across market segments

Abstract: Background: Climate change has become a concern of both policy makers and consumers. Transportation constitutes a key source of greenhouse gas (GHG) emissions; hence, alternative transportation fuels with reduced GHG emissions are of increasing interest as a potential strategy for decreasing emissions. However, consumer views on achieving emission reductions through the use of alternative fuels have not been widely studied. Understanding consumer preferences related to alternative fuels is relevant as new fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Two of these -the Environmentals and National Interests -are remarkably similar to Kahan et al's EC and HI constructs [20], with, for example, National Interests more likely to be male, Republican, and skeptical of climate change, much like HIs. Crucially, Marra et al found that while the level of GHG emissions attributed to a fuel blend was associated with WTP for E85 fuel, this effect was highly contingent on the market segment with which the consumer was affiliated, with a greatly strengthened effect relative to other market segments observed for Environmentals and a null effect among National Interests [23]. In a second study supporting the cultural cognition interpretation, Cacciatore et al found evidence for motivated reasoning by political partisans in the context of biofuels [17].…”
Section: Cultural Cognition Climate Change and Biofuelsmentioning
confidence: 95%
See 1 more Smart Citation
“…Two of these -the Environmentals and National Interests -are remarkably similar to Kahan et al's EC and HI constructs [20], with, for example, National Interests more likely to be male, Republican, and skeptical of climate change, much like HIs. Crucially, Marra et al found that while the level of GHG emissions attributed to a fuel blend was associated with WTP for E85 fuel, this effect was highly contingent on the market segment with which the consumer was affiliated, with a greatly strengthened effect relative to other market segments observed for Environmentals and a null effect among National Interests [23]. In a second study supporting the cultural cognition interpretation, Cacciatore et al found evidence for motivated reasoning by political partisans in the context of biofuels [17].…”
Section: Cultural Cognition Climate Change and Biofuelsmentioning
confidence: 95%
“…In analyzing the results of a WTP experiment, Marra et al conducted a market segmentation analysis in which they identified four market segments relevant to the purchase of ethanol-blended fuels [23]. Two of these -the Environmentals and National Interests -are remarkably similar to Kahan et al's EC and HI constructs [20], with, for example, National Interests more likely to be male, Republican, and skeptical of climate change, much like HIs.…”
Section: Cultural Cognition Climate Change and Biofuelsmentioning
confidence: 95%
“…This is the argument that dominated scientists' early discussions of biofuels and, unsurprisingly, the literature has found that Americans' perceptions of biofuels are tightly linked to their concern about climate change. Consumers' beliefs about the causes of and potential solutions to climate change are key predictors of their WTP for ethanol-blended fuel [27,28], and the extent to which they discriminate between biofuel blends based on their greenhouse gas reduction potential depends on their level of concern about climate change [9,29]. In short, the potential reduction in greenhouse gas emissions entailed by switching to biofuels is a pervasive consideration in Americans' decision-making process on whether to support biofuels and biofuels policies.…”
Section: The Climate Change Considerationmentioning
confidence: 99%
“…Consumers with strong environmental concerns are willing to pay a premium for renewable fuels in order to reduce greenhouse gas emissions (Marra et al 2012). The studies conducted among the residents of the Netherlands indicated that the WTP indicator is associated with understanding and worry and this association is stronger when accompanied by hope (Pleeging et al 2020).…”
Section: The Wtp -Determinants and Motifsmentioning
confidence: 99%